Mencegah Terjadinya Perceraian Melalui Pemberdayaan Ninik Mamak Dan Aparat Kelurahan Di Kota Payakumbuh - Dwiyanti Hanandini; Aziwarti Aziwarti; Machdaliza Machdaliza; Wahyu Pramono; Indradin Indradin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2016)
In Minangkabau society, ninikmamak’rule is very inportant for helping solve the problem in nuclear family. Empowering ninik mamak and local goverment rule is todo reducing measure of divorce in west sumatra exspecialy in Payakumbuh Town. The rule of ninik mamak, kader posyandu, tokoh masyarakat and local goverment can help society by use local values to solve hausehold problem. The extended family need to be motivated to more active to guidence of the merried couple who have hausehold problem and to avoid of divorce. They have to build collective consiousness about be inportant thing for helping family to solve their problem. So that, very need for helping them to avoid the divorced in hausehold.